Lessons from GPS-tagged Eurasian Curlews: synthesising movement ecology to inform conservation - Frédéric Jiguet; Aurélien Besnard; Pierrick Bocher; Andrea Kölzsch; Aleksi Lehikoinen; Markus Piha; Petr Procházka; Marie Donnez; Tuomas Seimola; Jimmy Allain; Lise Bartholus; Carole Doucerain; et al. (Biological Conservation, 2026)

Corrigendum to “Quality-assurance of heat-flow data: the new structure and evaluation scheme of the IHFC Global Heat Flow Database” [Tectonophysics 863 (2023) / 229976] - Sven Fuchs; Ben Norden; Florian Neumann; Norbert Kaul; Akiko Tanaka; Ilmo T. Kukkonen; Christophe Pascal; Rodolfo Christiansen; Gianluca Gola; Jan Šafanda; Orlando Miguel Espinoza-Ojeda; Ignacio Marzan; et al. (Tectonophysics, 2026)

Quality-assurance of heat-flow data: The new structure and evaluation scheme of the IHFC Global Heat Flow Database - Sven Fuchs; Ben Norden; Florian Neumann; Norbert Kaul; Akiko Tanaka; Ilmo T. Kukkonen; Christophe Pascal; Rodolfo Christiansen; Gianluca Gola; Jan Šafanda; Orlando Miguel Espinoza-Ojeda; Ignacio Marzan; et al. (Tectonophysics, 2023)

A review of standardized high-throughput cardiovascular phenotyping with a link to metabolism in mice - Jiri Lindovsky; Zuzana Nichtova; Nathalia R. V. Dragano; David Pajuelo Reguera; Jan Prochazka; Helmut Fuchs; Susan Marschall; Valerie Gailus-Durner; Radislav Sedlacek; Martin Hrabě de Angelis; Jan Rozman; Nadine Spielmann (Mammalian Genome, 2023)
Cardiovascular diseases cause a high mortality rate worldwide and represent a major burden for health care systems. Experimental rodent models play a central role in cardiovascular disease research by effectively simulating human cardiovascular diseases. Using mice, the International Mouse Phenotyping Consortium (IMPC) aims to target each protein-coding gene and phenotype multiple organ systems in single-gene knockout models by a global network of mouse clinics. In this review, we summarize the current advances of the IMPC in cardiac research and describe in detail the diagnostic requirements of high-throughput electrocardiography and transthoracic echocardiography capable of detecting cardiac arrhythmias and cardiomyopathies in mice. Beyond that, we are linking metabolism to the heart and describing phenotypes that emerge in a set of known genes, when knocked out in mice, such as the leptin receptor ( Lepr ), leptin ( Lep ), and Bardet–Biedl syndrome 5 ( Bbs5 ). Furthermore, we are presenting not yet associated loss-of-function genes affecting both, metabolism and the cardiovascular system, such as the RING finger protein 10 ( Rfn10 ), F-box protein 38 ( Fbxo38 ), and Dipeptidyl peptidase 8 ( Dpp8 ). These extensive high-throughput data from IMPC mice provide a promising opportunity to explore genetics causing metabolic heart disease with an important translational approach.

Comprehensive ECG reference intervals in C57BL/6N substrains provide a generalizable guide for cardiac electrophysiology studies in mice - Manuela A. Oestereicher; Janine M. Wotton; Shinya Ayabe; Ghina Bou About; Tsz Kwan Cheng; Jae-Hoon Choi; Dave Clary; Emily M. Dew; Lahcen Elfertak; Alain Guimond; Hamed Haseli Mashhadi; Jason D. Heaney; et al. (Mammalian Genome, 2023)
Reference ranges provide a powerful tool for diagnostic decision-making in clinical medicine and are enormously valuable for understanding normality in pre-clinical scientific research that uses in vivo models. As yet, there are no published reference ranges for electrocardiography (ECG) in the laboratory mouse. The first mouse-specific reference ranges for the assessment of electrical conduction are reported herein generated from an ECG dataset of unprecedented scale. International Mouse Phenotyping Consortium data from over 26,000 conscious or anesthetized C57BL/6N wildtype control mice were stratified by sex and age to develop robust ECG reference ranges. Interesting findings include that heart rate and key elements from the ECG waveform (RR-, PR-, ST-, QT-interval, QT corrected, and QRS complex) demonstrate minimal sexual dimorphism. As expected, anesthesia induces a decrease in heart rate and was shown for both inhalation (isoflurane) and injectable (tribromoethanol) anesthesia. In the absence of pharmacological, environmental, or genetic challenges, we did not observe major age-related ECG changes in C57BL/6N-inbred mice as the differences in the reference ranges of 12-week-old compared to 62-week-old mice were negligible. The generalizability of the C57BL/6N substrain reference ranges was demonstrated by comparison with ECG data from a wide range of non-IMPC studies. The close overlap in data from a wide range of mouse strains suggests that the C57BL/6N-based reference ranges can be used as a robust and comprehensive indicator of normality. We report a unique ECG reference resource of fundamental importance for any experimental study of cardiac function in mice.

Echo2Pheno: a deep-learning application to uncover echocardiographic phenotypes in conscious mice - Christina Bukas; Isabella Galter; Patricia da Silva-Buttkus; Helmut Fuchs; Holger Maier; Valerie Gailus-Durner; Christian L. Müller; Martin Hrabě de Angelis; Marie Piraud; Nadine Spielmann (Mammalian Genome, 2023)
Echocardiography, a rapid and cost-effective imaging technique, assesses cardiac function and structure. Despite its popularity in cardiovascular medicine and clinical research, image-derived phenotypic measurements are manually performed, requiring expert knowledge and training. Notwithstanding great progress in deep-learning applications in small animal echocardiography, the focus has so far only been on images of anesthetized rodents. We present here a new algorithm specifically designed for echocardiograms acquired in conscious mice called Echo2Pheno, an automatic statistical learning workflow for analyzing and interpreting high-throughput non-anesthetized transthoracic murine echocardiographic images in the presence of genetic knockouts. Echo2Pheno comprises a neural network module for echocardiographic image analysis and phenotypic measurements, including a statistical hypothesis-testing framework for assessing phenotypic differences between populations. Using 2159 images of 16 different knockout mouse strains of the German Mouse Clinic, Echo2Pheno accurately confirms known cardiovascular genotype–phenotype relationships (e.g., Dystrophin) and discovers novel genes (e.g., CCR4-NOT transcription complex subunit 6-like, Cnot6l, and synaptotagmin-like protein 4, Sytl4 ), which cause altered cardiovascular phenotypes, as verified by H&E-stained histological images. Echo2Pheno provides an important step toward automatic end-to-end learning for linking echocardiographic readouts to cardiovascular phenotypes of interest in conscious mice. Graphical abstract

Knockout mouse models as a resource for the study of rare diseases - Patricia da Silva-Buttkus; Nadine Spielmann; Tanja Klein-Rodewald; Christine Schütt; Antonio Aguilar-Pimentel; Oana V. Amarie; Lore Becker; Julia Calzada-Wack; Lillian Garrett; Raffaele Gerlini; Markus Kraiger; Stefanie Leuchtenberger; et al. (Mammalian Genome, 2023)
Rare diseases (RDs) are a challenge for medicine due to their heterogeneous clinical manifestations and low prevalence. There is a lack of specific treatments and only a few hundred of the approximately 7,000 RDs have an approved regime. Rapid technological development in genome sequencing enables the mass identification of potential candidates that in their mutated form could trigger diseases but are often not confirmed to be causal. Knockout (KO) mouse models are essential to understand the causality of genes by allowing highly standardized research into the pathogenesis of diseases. The German Mouse Clinic (GMC) is one of the pioneers in mouse research and successfully uses (preclinical) data obtained from single-gene KO mutants for research into monogenic RDs. As part of the International Mouse Phenotyping Consortium (IMPC) and INFRAFRONTIER, the pan-European consortium for modeling human diseases, the GMC expands these preclinical data toward global collaborative approaches with researchers, clinicians, and patient groups. Here, we highlight proprietary genes that when deleted mimic clinical phenotypes associated with known RD targets ( Nacc1, Bach2, Klotho alpha ). We focus on recognized RD genes with no pre-existing KO mouse models ( Kansl1l, Acsf3, Pcdhgb2, Rabgap1, Cox7a2 ) which highlight novel phenotypes capable of optimizing clinical diagnosis. In addition, we present genes with intriguing phenotypic data ( Zdhhc5, Wsb2 ) that are not presently associated with known human RDs. This report provides comprehensive evidence for genes that when deleted cause differences in the KO mouse across multiple organs, providing a huge translational potential for further understanding monogenic RDs and their clinical spectrum. Genetic KO studies in mice are valuable to further explore the underlying physiological mechanisms and their overall therapeutic potential.

Knockout of the Complex III subunit Uqcrh causes bioenergetic impairment and cardiac contractile dysfunction - Nadine Spielmann; Christina Schenkl; Tímea Komlódi; Patricia da Silva-Buttkus; Estelle Heyne; Jana Rohde; Oana V. Amarie; Birgit Rathkolb; Erich Gnaiger; Torsten Doenst; Helmut Fuchs; Valérie Gailus-Durner; et al. (Mammalian Genome, 2023)
Ubiquinol cytochrome c reductase hinge protein (UQCRH) is required for the electron transfer between cytochrome c 1 and c of the mitochondrial cytochrome bc 1 Complex (CIII). A two-exon deletion in the human UQCRH gene has recently been identified as the cause for a rare familial mitochondrial disorder. Deletion of the corresponding gene in the mouse ( Uqcrh -KO) resulted in striking biochemical and clinical similarities including impairment of CIII, failure to thrive, elevated blood glucose levels, and early death. Here, we set out to test how global ablation of the murine Uqcrh affects cardiac morphology and contractility, and bioenergetics. Hearts from Uqcrh -KO mutant mice appeared macroscopically considerably smaller compared to wildtype littermate controls despite similar geometries as confirmed by transthoracic echocardiography (TTE). Relating TTE-assessed heart to body mass revealed the development of subtle cardiac enlargement, but histopathological analysis showed no excess collagen deposition. Nonetheless, Uqcrh -KO hearts developed pronounced contractile dysfunction. To assess mitochondrial functions, we used the high-resolution respirometer NextGen-O2k allowing measurement of mitochondrial respiratory capacity through the electron transfer system (ETS) simultaneously with the redox state of ETS-reactive coenzyme Q (Q), or production of reactive oxygen species (ROS). Compared to wildtype littermate controls, we found decreased mitochondrial respiratory capacity and more reduced Q in Uqcrh -KO, indicative for an impaired ETS. Yet, mitochondrial ROS production was not generally increased. Taken together, our data suggest that Uqcrh -KO leads to cardiac contractile dysfunction at 9 weeks of age, which is associated with impaired bioenergetics but not with mitochondrial ROS production. Graphical abstract Global ablation of the Uqcrh gene results in functional impairment of CIII associated with metabolic dysfunction and postnatal developmental arrest immediately after weaning from the mother. Uqcrh -KO mice show dramatically elevated blood glucose levels and decreased ability of isolated cardiac mitochondria to consume oxygen (O 2 ). Impaired development (failure to thrive) after weaning manifests as a deficiency in the gain of body mass and growth of internal organ including the heart. The relative heart mass seemingly increases when organ mass calculated from transthoracic echocardiography (TTE) is normalized to body mass. Notably, the heart shows no signs of collagen deposition, yet does develop a contractile dysfunction reflected by a decrease in ejection fraction and fractional shortening.

A rationale for considering heart/brain axis control in neuropsychiatric disease - Lillian Garrett; Dietrich Trümbach; Nadine Spielmann; Wolfgang Wurst; Helmut Fuchs; Valerie Gailus-Durner; Martin Hrabě de Angelis; Sabine M. Hölter (Mammalian Genome, 2023)
Neuropsychiatric diseases (NPD) represent a significant global disease burden necessitating innovative approaches to pathogenic understanding, biomarker identification and therapeutic strategy. Emerging evidence implicates heart/brain axis malfunction in NPD etiology, particularly via the autonomic nervous system (ANS) and brain central autonomic network (CAN) interaction. This heart/brain inter-relationship harbors potentially novel NPD diagnosis and treatment avenues. Nevertheless, the lack of multidisciplinary clinical approaches as well as a limited appreciation of molecular underpinnings has stymied progress. Large-scale preclinical multi-systemic functional data can therefore provide supplementary insight into CAN and ANS interaction. We here present an overview of the heart/brain axis in NPD and establish a unique rationale for utilizing a preclinical cardiovascular disease risk gene set to glean insights into heart/brain axis control in NPD. With a top-down approach focusing on genes influencing electrocardiogram ANS function, we combined hierarchical clustering of corresponding regional CAN expression data and functional enrichment analysis to reveal known and novel molecular insights into CAN and NPD. Through ‘support vector machine’ inquiries for classification and literature validation, we further pinpointed the top 32 genes highly expressed in CAN brain structures altering both heart rate/heart rate variability (HRV) and behavior. Our observations underscore the potential of HRV/hyperactivity behavior as endophenotypes for multimodal disease biomarker identification to index aberrant executive brain functioning with relevance for NPD. This work heralds the potential of large-scale preclinical functional genetic data for understanding CAN/ANS control and introduces a stepwise design leveraging preclinical data to unearth novel heart/brain axis control genes in NPD.

A comprehensive phenotypic characterization of a whole-body Wdr45 knock-out mouse - Caroline A. Biagosch; Silvia Vidali; Michael Faerberboeck; Svenja-Viola Hensler; Lore Becker; Oana V. Amarie; Antonio Aguilar-Pimentel; Lillian Garrett; Tanja Klein-Rodewald; Birgit Rathkolb; Enrica Zanuttigh; Julia Calzada-Wack; et al. (Mammalian Genome, 2021)
Pathogenic variants in the WDR45 (OMIM: 300,526) gene on chromosome Xp11 are the genetic cause of a rare neurological disorder characterized by increased iron deposition in the basal ganglia. As WDR45 encodes a beta-propeller scaffold protein with a putative role in autophagy, the disease has been named Beta-Propeller Protein-Associated Neurodegeneration (BPAN). BPAN represents one of the four most common forms of Neurodegeneration with Brain Iron Accumulation (NBIA). In the current study, we generated and characterized a whole-body Wdr45 knock-out (KO) mouse model. The model, developed using TALENs, presents a 20-bp deletion in exon 2 of Wdr45 . Homozygous females and hemizygous males are viable, proving that systemic depletion of Wdr45 does not impair viability and male fertility in mice. The in-depth phenotypic characterization of the mouse model revealed neuropathology signs at four months of age, neurodegeneration progressing with ageing, hearing and visual impairment, specific haematological alterations, but no brain iron accumulation. Biochemically, Wdr45 KO mice presented with decreased complex I (CI) activity in the brain, suggesting that mitochondrial dysfunction accompanies Wdr45 deficiency. Overall, the systemic Wdr45 KO described here complements the two mouse models previously reported in the literature (PMIDs: 26,000,824, 31,204,559) and represents an additional robust model to investigate the pathophysiology of BPAN and to test therapeutic strategies for the disease.

A comprehensive and comparative phenotypic analysis of the collaborative founder strains identifies new and known phenotypes - Heike Kollmus; Helmut Fuchs; Christoph Lengger; Hamed Haselimashhadi; Molly A. Bogue; Manuela A. Östereicher; Marion Horsch; Thure Adler; Juan Antonio Aguilar-Pimentel; Oana Veronica Amarie; Lore Becker; Johannes Beckers; et al. (Mammalian Genome, 2020)
The collaborative cross (CC) is a large panel of mouse-inbred lines derived from eight founder strains (NOD/ShiLtJ, NZO/HILtJ, A/J, C57BL/6J, 129S1/SvImJ, CAST/EiJ, PWK/PhJ, and WSB/EiJ). Here, we performed a comprehensive and comparative phenotyping screening to identify phenotypic differences and similarities between the eight founder strains. In total, more than 300 parameters including allergy, behavior, cardiovascular, clinical blood chemistry, dysmorphology, bone and cartilage, energy metabolism, eye and vision, immunology, lung function, neurology, nociception, and pathology were analyzed; in most traits from sixteen females and sixteen males. We identified over 270 parameters that were significantly different between strains. This study highlights the value of the founder and CC strains for phenotype-genotype associations of many genetic traits that are highly relevant to human diseases. All data described here are publicly available from the mouse phenome database for analyses and downloads.

Crybb2 Mutations Consistently Affect Schizophrenia Endophenotypes in Mice - Tamara Heermann; Lillian Garrett; Wolfgang Wurst; Helmut Fuchs; Valerie Gailus-Durner; Martin Hrabě de Angelis; Jochen Graw; Sabine M. Hölter (Molecular Neurobiology, 2019)

Fgf9 Y162C Mutation Alters Information Processing and Social Memory in Mice - Lillian Garrett; Lore Becker; Jan Rozman; Oliver Puk; Tobias Stoeger; Ali Önder Yildirim; Alexander Bohla; Oliver Eickelberg; Wolfgang Hans; Cornelia Prehn; Jerzy Adamski; Thomas Klopstock; et al. (Molecular Neurobiology, 2018)

Serum Response Factor (SRF) Ablation Interferes with Acute Stress-Associated Immediate and Long-Term Coping Mechanisms - Annemarie Zimprich; Gabi Mroz; Christopher Meyer zu Reckendorf; Sofia Anastasiadou; Philip Förstner; Lillian Garrett; Sabine M. Hölter; Lore Becker; Jan Rozman; Cornelia Prehn; Birgit Rathkolb; Kristin Moreth; et al. (Molecular Neurobiology, 2017)

A novel biological function of soluble biglycan: Induction of erythropoietin production and polycythemia - Helena Frey; Kristin Moreth; Louise Tzung-Harn Hsieh; Jinyang Zeng-Brouwers; Birgit Rathkolb; Helmut Fuchs; Valérie Gailus-Durner; Renato V. Iozzo; Martin Hrabě de Angelis; Liliana Schaefer (Glycoconjugate Journal, 2017)

Land management: data availability and process understanding for global change studies - Karl‐Heinz Erb; Sebastiaan Luyssaert; Patrick Meyfroidt; Julia Pongratz; Axel Don; Silvia Kloster; Tobias Kuemmerle; Tamara Fetzel; Richard Fuchs; Martin Herold; Helmut Haberl; Chris D. Jones; et al. (Global Change Biology, 2017)
In the light of daunting global sustainability challenges such as climate change, biodiversity loss and food security, improving our understanding of the complex dynamics of the Earth system is crucial. However, large knowledge gaps related to the effects of land management persist, in particular those human‐induced changes in terrestrial ecosystems that do not result in land‐cover conversions. Here, we review the current state of knowledge of ten common land management activities for their biogeochemical and biophysical impacts, the level of process understanding and data availability. Our review shows that ca. one‐tenth of the ice‐free land surface is under intense human management, half under medium and one‐fifth under extensive management. Based on our review, we cluster these ten management activities into three groups: (i) management activities for which data sets are available, and for which a good knowledge base exists (cropland harvest and irrigation); (ii) management activities for which sufficient knowledge on biogeochemical and biophysical effects exists but robust global data sets are lacking (forest harvest, tree species selection, grazing and mowing harvest, N fertilization); and (iii) land management practices with severe data gaps concomitant with an unsatisfactory level of process understanding (crop species selection, artificial wetland drainage, tillage and fire management and crop residue management, an element of crop harvest). Although we identify multiple impediments to progress, we conclude that the current status of process understanding and data availability is sufficient to advance with incorporating management in, for example, Earth system or dynamic vegetation models in order to provide a systematic assessment of their role in the Earth system. This review contributes to a strategic prioritization of research efforts across multiple disciplines, including land system research, ecological research and Earth system modelling.

Viable Ednra Y129F mice feature human mandibulofacial dysostosis with alopecia (MFDA) syndrome due to the homologue mutation - Sibylle Sabrautzki; Michael A. Sandholzer; Bettina Lorenz-Depiereux; Robert Brommage; Gerhard Przemeck; Ingrid L. Vargas Panesso; Alexandra Vernaleken; Lillian Garrett; Katharina Baron; Ali O. Yildirim; Jan Rozman; Birgit Rathkolb; et al. (Mammalian Genome, 2016)

A nearly complete respiratory, circulatory, and excretory system preserved in small Late Cretaceous octopods (Cephalopoda) from Lebanon - Dirk Fuchs; Philipp R. Wilby; Sigurd von Boletzky; Pierre Abi-Saad; Helmut Keupp; Yasuhiro Iba (PalZ, 2016)

Exome sequencing identifies a nonsense mutation in Fam46a associated with bone abnormalities in a new mouse model for skeletal dysplasia - Susanne Diener; Sieglinde Bayer; Sibylle Sabrautzki; Thomas Wieland; Birgit Mentrup; Gerhard K. H. Przemeck; Birgit Rathkolb; Elisabeth Graf; Wolfgang Hans; Helmut Fuchs; Marion Horsch; Thomas Schwarzmayr; et al. (Mammalian Genome, 2016)

Principles and application of LIMS in mouse clinics - Holger Maier; Christine Schütt; Ralph Steinkamp; Anja Hurt; Elida Schneltzer; Philipp Gormanns; Christoph Lengger; Mark Griffiths; David Melvin; Neha Agrawal; Rafael Alcantara; Arthur Evans; et al. (Mammalian Genome, 2015)

Screen for alterations of iron related parameters in N-ethyl-N-nitrosourea-treated mice identified mutant lines with increased plasma ferritin levels - Birgit Rathkolb; Martina Klempt; Sibylle Sabrautzki; Dian Michel; Matthias Klaften; Jürgen Laufs; Reinhard Sedlmeier; Wolfgang Hans; Helmut Fuchs; Martina U. Muckenthaler; Marion Horsch; Dean R. Campagna; et al. (BioMetals, 2015)

Erratum to: New mouse models for metabolic bone diseases generated by genome-wide ENU mutagenesis - Sibylle Sabrautzki; Isabel Rubio-Aliaga; Wolfgang Hans; Helmut Fuchs; Birgit Rathkolb; Julia Calzada-Wack; Christian M. Cohrs; Matthias Klaften; Hartwig Seedorf; Sebastian Eck; Ana Benet-Pagès; Jack Favor; et al. (Mammalian Genome, 2014)

High-throughput phenotypic assessment of cardiac physiology in four commonly used inbred mouse strains - Kristin Moreth; Ralf Fischer; Helmut Fuchs; Valérie Gailus-Durner; Wolfgang Wurst; Hugo A. Katus; Raffi Bekeredjian; Martin Hrabě de Angelis (Journal of Comparative Physiology B, 2014)

Long-term experiment to study the development, interaction, and influencing factors of DEXA parameters - Helmut Fuchs; Christine Gau; Wolfgang Hans; Valerie Gailus-Durner; Martin Hrabě de Angelis (Mammalian Genome, 2013)

First record of a complete arm crown of the Early Jurassic coleoid Loligosepia (Cephalopoda) - Dirk Fuchs; Helmut Keupp; Günter Schweigert (PalZ, 2013)

Mouse large-scale phenotyping initiatives: overview of the European Mouse Disease Clinic (EUMODIC) and of the Wellcome Trust Sanger Institute Mouse Genetics Project - Abdel Ayadi; Marie-Christine Birling; Joanna Bottomley; James Bussell; Helmut Fuchs; Martin Fray; Valérie Gailus-Durner; Simon Greenaway; Richard Houghton; Natasha Karp; Sophie Leblanc; Christoph Lengger; et al. (Mammalian Genome, 2012)

Innovations in phenotyping of mouse models in the German Mouse Clinic - Helmut Fuchs; Valérie Gailus-Durner; Susanne Neschen; Thure Adler; Luciana Caminha Afonso; Juan Antonio Aguilar-Pimentel; Lore Becker; Alexander Bohla; Julia Calzada-Wack; Christian Cohrs; Anna Dewert; Barbara Fridrich; et al. (Mammalian Genome, 2012)

New mouse models for metabolic bone diseases generated by genome-wide ENU mutagenesis - Sibylle Sabrautzki; Isabel Rubio-Aliaga; Wolfgang Hans; Helmut Fuchs; Birgit Rathkolb; Julia Calzada-Wack; Christian M. Cohrs; Matthias Klaften; Hartwig Seedorf; Sebastian Eck; Ana Benet-Pagès; Jack Favor; et al. (Mammalian Genome, 2012)

Microphthalmia, parkinsonism, and enhanced nociception in Pitx3 416insG mice - Michael Rosemann; Alesia Ivashkevich; Jack Favor; Claudia Dalke; Sabine M. Hölter; Lore Becker; Ildikó Rácz; Ines Bolle; Martina Klempt; Birgit Rathkolb; Svetoslav Kalaydjiev; Thure Adler; et al. (Mammalian Genome, 2010)

Power matters in closing the phenotyping gap - Carola W. Meyer; Ralf Elvert; André Scherag; Nicole Ehrhardt; Valerie Gailus-Durner; Helmut Fuchs; Helmut Schäfer; Martin Hrabé de Angelis; Gerhard Heldmaier; Martin Klingenspor (The Science of Nature, 2007)

Morphologic and molecular characterization of two novel Krt71 (Krt2-6g) mutations: Krt71 rco12 and Krt71 rco13 - Fabian Runkel; Matthias Klaften; Kerstin Koch; Volker Böhnert; Heinrich Büssow; Helmut Fuchs; Thomas Franz; Martin Hrabé de Angelis (Mammalian Genome, 2006)

New ENU-induced semidominant mutation, Ali18, causes inflammatory arthritis, dermatitis, and osteoporosis in the mouse - Koichiro Abe; Helmut Fuchs; Thomas Lisse; Wolfgang Hans; Martin Hrabé de Angelis (Mammalian Genome, 2006)

A Myo7a mutation cosegregates with stereocilia defects and low-frequency hearing impairment - Charlotte R. Rhodes; Ronna Hertzano; Helmut Fuchs; Rachel E. Bell; Martin Hrabé de Angelis; Karen P. Steel; Karen B. Avraham (Mammalian Genome, 2004)

An ENU-induced mutation in AP-2α leads to middle earand ocular defects in Doarad mice - Nadav Ahituv; Alexandra Erven; Helmut Fuchs; Keren Guy; Ruth Ashery–Padan; Trevor Williams; Martin Hrabe de Angelis; Karen B. Avraham; Karen P. Steel (Mammalian Genome, 2004)

V76D mutation in a conserved gD-crystallin region leads to dominant cataracts in mice - Jochen Graw; Jana Löster; Dian Soewarto; Helmut Fuchs; André Reis; Eckhard Wolf; Rudi Balling; Martin Angelis (Mammalian Genome, 2002)

Inbred strain variation in lung function - Claudia Reinhard; Gunter Eder; Helmut Fuchs; Axel Ziesenis; Joachim Heyder; Holger Schulz (Mammalian Genome, 2002)

Spatio-Temporal Current Density Reconstruction (stCDR) from EEG/MEG-Data - Felix Darvas; Uwe Schmitt; Alfred K. Louis; Manfred Fuchs; Gunter Knoll; Helmut Buchner (Brain Topography, 2001)

MouseNet© database: digital management of a large-scale mutagenesis project - Walter Pargent; Stephan Heffner; Karlheinz F. Schäble; Dian Soewarto; Helmut Fuchs; Martin Hrabé de Angelis (Mammalian Genome, 2000)

The clinical-chemical screen in the Munich ENU Mouse Mutagenesis Project: screening for clinically relevant phenotypes - Birgit Rathkolb; Tanja Decker; Edith Fuchs; Dian Soewarto; Christiane Fella; Stephan Heffner; Walter Pargent; Rüdiger Wanke; Rudi Balling; Martin Hrabé de Angelis; Helmut J. Kolb; Eckhard Wolf (Mammalian Genome, 2000)

Screening for dysmorphological abnormalities—a powerful tool to isolate new mouse mutants - Helmut Fuchs; Klaus Schughart; Eckhard Wolf; Rudi Balling; Martin Hrabé de Angelis (Mammalian Genome, 2000)

Properties of Advanced Headmodelling and Source Reconstruction for the Localization of Epileptiform Activity - Till D. Waberski; Helmut Buchner; Klaus Lehnertz; Andreas Hufnagel; Manfred Fuchs; Rainer Beckmann; Adrian Rienäcker (Brain Topography, 1998)